CpG-DNA exerts antibacterial effects by protecting immune cells and producing bacteria-reactive antibodies. Issue 1 (December 2018) - Kim, Te; Kim, Dongbum; Gautam, Avishekh; Lee, Heesu; Kwak, Min; Park, Min; Park, Sangkyu; Wu, Guang; Lee, Bok; Lee, Younghee; Kwon, Hyung-Joo
Abstract CpG-DNA activates various immune cells, contributing to the host defense against bacteria. Here, we examined the biological function of CpG-DNA in the production of bacteria-reactive antibodies. The administration of CpG-DNA increased survival in mice following infection with methicillin-resistantS. aureus and protected immune cell populations in the peritoneal cavity, bone marrow, and spleen. CpG-DNA injection likewise increased bacteria-reactive antibodies in the mouse peritoneal fluid and serum, which was dependent on TLR9. B cells isolated from the peritoneal cavity produced bacteria-reactive antibodiesin vitro following CpG-DNA administration that enhanced the phagocytic activity of the peritoneal cells. The bacteria-reactive monoclonal antibody enhanced phagocytosisin vitro and protected mice afterS. aureus infection. Therefore, we suggest that CpG-DNA enhances the antibacterial activity of the immune system by protecting immune cells and triggering the production of bacteria-reactive antibodies. Consequently, we believe that monoclonal antibodies could aid in the treatment of antibiotic-resistant bacterial infections.